Diversivikasi Olahan Pangan Lokal Ubi Kayu di Desa Kaongkeongke Kecamatan Pasarwajo Kabupaten Pasar Wajo - Azizu, Azelia Monica; Purnamasari, Wa Ode Dian; Hamar, Bahtiar; Bone, Abdul Hadi; Cahyani, Waode Sitti (Lembaga Riset dan Inovasi Masyarakat Madani, 2022)
Development of processed cassava commodity products so that it can improve the quality and high selling value when marketed by the community, especially cassava farmers. This effort is one of the strategies in maintaining and realizing food security through cassava diversification. This community service activity is to improve the skills of the community or cassava farmers in managing it into various foods that have high selling values with training. Service activities are carried out in Kaongkeongke Village, Buton Regency. The activity starts with the preparation of the materials and tools used. Next, the process of pounding the cassava becomes smooth to extract the starch which will be used as the basic ingredient for cake dough. After that all the wok is mixed to become a dough and steamed at a temperature of 80 - 100 oC. This training was carried out quite well and many people and cassava farmers attended and were enthusiastic in asking questions, so that the knowledge given in the form of training could be easily accepted by the participants.